Intra-organizational networking for innovation-based corporate entrepreneurship - Kelley, Donna J.; Peters, Lois; O'Connor, Gina Colarelli (Journal of Business Venturing, 2009)
This study takes a network theoretical perspective in its examination of innovation-based corporate entrepreneurship (ICE), focusing on how project-specific ties can form for non-routine phenomena. A comparative case analysis of 246 interviews in twelve industry-leading global corporations identifies constructs associated with individual network capacity at the individual level, organizational network capacity at the organization level, and program network capacity at the ICE program level. In addition, we recognize the managerial facilitating roles of cultivator and broker. We develop propositions aimed at providing insights about the relationships among these constructs, and identify implications for managerial and ICE program responsibilities.